Synthesis, characterization, electrochemical, spectroelectrochemical and dye-sensitized solar cell properties of Phthalocyanines Containing Carboxylic Acid Anchoring Groups as photosensitizer - ERDAĞ MADEN, YAREN; KOCA, ATIF (My University, 2022)
Peripherally tetra-4-carboxyethylphenoxy substituted oxotitanium (IV), cobalt(II), zinc(II) and metal free phthalocyanines were synthesized to research the sensitizing abilities of these dye molecules in standard dye sensitized solar cells (DSSCs). All the synthesized phthalocyanine complexes have been characterized by using elemental analyses, UV-Vis, FT-IR, H-1 NMR and MALDI-TOF MS spectroscopic techniques. Electrochemistry of metallo phthalocyanines (MPcs) were studied with electrochemical and in-situ spectroelectrochemical measurements. H2Pc (7) and ZnPc (5) illustrated similar Pc based electron transfer reactions. Differently, CoPc (6) and TiOPc (4) illustrated metal based redox reactions, which enhanced the redox functionality of these complexes. Metal based reductions for CoPc (6) and TiOPc (4) were recorded in addition to the Pc based one. In-situ spectroelectrochemical measurements supported the proposed voltametric mechanism. Moreover, the color and spectra of the electrogenerated species were determined with the in-situ spectroelectrochemical analyses to predict possible optoelectrochemical application of the complexes. Pronounced optical and color changes during the electrolysis of the complexes indicated electrooptical and possible solid state electrochemical functionality of the complexes. TiO2 semiconductor on the fluoride doped indium tin oxide coated glass electrode (FTO) was decorated with H2Pc (7) and TiOPc (4) bearing four carboxyl anchoring groups and they were first of all tested as possible dye for the DSSC. H2Pc (7), TiOPc (4), CoPc (6) and ZnPc (5) dyes used in DSSCs showed 2.9%, 3.3%, 1.02% and 2.2% of power conversion efficiencies respectively.
Keywords: Kimya Mühendisliği ve Teknolojisi; Tekstil Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Textile Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); MÜHENDİSLİK, KİMYASAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, TEKSTİL; Malzeme Bilimi; CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); ENGINEERING, CHEMICAL; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, TEXTILES; MATERIALS SCIENCE; Genel Mühendislik; Kimyasal Sağlık ve Güvenlik; Akışkan Akışı ve Transfer İşlemleri; Kimya (çeşitli); Kimya Mühendisliği (çeşitli); Genel Malzeme Bilimi; Mühendislik (çeşitli); Genel Kimya Mühendisliği; Kolloid ve Yüzey Kimyası; Genel Kimya; Kataliz; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; General Engineering; Chemical Health and Safety; Fluid Flow and Transfer Processes; Chemistry (miscellaneous); Chemical Engineering (miscellaneous); General Materials Science; Engineering (miscellaneous); General Chemical Engineering; Colloid and Surface Chemistry; General Chemistry; Catalysis; Process Chemistry and Technology; Physical Sciences; Phthalocyanine; Carboxylic acid; Electrochemistry; Spectroelectrochemistry; Dye sensitized solar cell; NANOCRYSTALLINE TIO2 FILMS; ZINC PHTHALOCYANINES; SUBSTITUTED COBALT; TITANIUM(IV) PHTHALOCYANINES; ELECTRON INJECTION; COMPLEXES; MANGANESE; COPPER; IRON; METALLOPHTHALOCYANINES